1998
DOI: 10.1093/oxfordjournals.aje.a009541
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Increased Bone Loss in an Elderly Population The Rotterdam Study

Abstract: The association of bone loss with age, sex, and several prevalent and modifiable potential risk factors for osteoporosis was studied in 1,856 men and 2,452 women aged 55 years and over from the Rotterdam Study, a population-based cohort study in the Netherlands. The rate of change in femoral neck bone mineral density was estimated longitudinally between 1990 and 1995, after 2 years of follow-up on average. These rates, adjusted for age and body mass index, were -0.0025 (95% confidence interval -0.0038 to -0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
192
5
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(237 citation statements)
references
References 31 publications
30
192
5
10
Order By: Relevance
“…Initial reports suggested this association was U-shaped, but the differences were not significant (Burger et al, 1998;Hannan et al, 2000). Recently, an inverted U-shape curve was showed in a cross-sectional study in old men, but not in women (Tucker et al, 2009), whereas a meta analysis has described a linear relationship between femoral neck bone density and alcohol consumption (Berg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports suggested this association was U-shaped, but the differences were not significant (Burger et al, 1998;Hannan et al, 2000). Recently, an inverted U-shape curve was showed in a cross-sectional study in old men, but not in women (Tucker et al, 2009), whereas a meta analysis has described a linear relationship between femoral neck bone density and alcohol consumption (Berg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…6 Environmental factors also affect the risk for future fracture and include physical activity, calcium intake, smoking, and possibly alcohol intake. [6][7][8][9][10] While some studies have found site-specific gender differences in BMD heritability, others have observed no gender differences. 2 Many of these studies were limited in their site selection, often focusing mostly on BMD of the hip, spine, femoral neck and forearm, and only one 11 was a twin study.…”
mentioning
confidence: 99%
“…Доказано, что ежегодная потеря МПК у больных с РА более выражена, чем в популяции. Например, в Роттер-дамском исследовании [11], включавшем 4333 человека без РА в возрасте старше 55 лет, было выявлено сниже-ние МПК через 2 года с момента начала исследования на 0,4% у мужчин и на 0,6% у женщин, а у больных с ранней стадией РА идентичного возраста, согласно исследова-нию BeSt, МПК в шейке бедра снижалось на 1,4 и 1,5% соответственно уже через год после начала исследова-ния, несмотря на то что все пациенты получали базис-ную терапию. Рассматривается целый ряд причин увели-чения риска ОП при РА.…”
unclassified